1218. Retapamulin as a Potential Decolonizing Agent: Activity against Mupirocin-Resistant Strains From Pediatric Patients With Methicillin-Resistant Staphylococcus aureus Infection. (26th November 2018) - Patel, Ami; Lighter-Fisher, Jennifer; Fulmer, Yi; Copin, Richard; Ratner, Adam; Shopsin, Bo
Abstract: Background: Controlling methicillin-resistant Staphylococcus aureus (MRSA) colonization is a common strategy to prevent transmission and recurrent infection. Standard decolonization regimens include nasal application of mupirocin ointment; however, increasing rates of mupirocin-resistance (Mup-R) have been noted globally. At our institution there has been an increase in community-acquired MRSA (CA-MRSA) infections among children living in Brooklyn, New York. A genotypic geographic cluster of an outbreak clone of the CA-MRSA strain USA 300 with a high rate (>85%) of mupirocin resistance, mediated by the plasmid borne mupA gene, was identified prompting investigation into an alternative decolonizing agent. We sought to investigate retapamulin, a topical pleuromutilin antibiotic, which has been shown to be effective against S. aureus with in vitro and in vivo activity against MRSA and a low propensity to develop resistance. Methods: Broth microdilution was used to determine the minimum inhibitory concentrations (MIC) of retapamulin against 53 Mup-R MRSA isolates collected from pediatric patients (aged 9 months–17 years) presenting to our institution over an 18 month period with clinical MRSA infection. Susceptibility defined as ≤0.5 mg/L susceptible (EUCAST). Whole genome sequence data were analyzed for the presence of rplC and cfr gene mutations known to confer resistance to retapamulin. Results: All 53 isolates were susceptible to retapamulin. 49/53 (92%) strains were inhibited at MIC 0.25 mg/L, 2/53 (4%) at MIC 0.125 mg/L, and 2/53 (4%) at MIC 0.5 mg/L. DNA sequence analysis showed that one isolate had a first-step mutation in the rplC gene, but it was not associated with reduced phenotypic susceptibility to retapamulin, as the MIC of that isolate was 0.25 mg/L. Conclusion: Retapamulin demonstrated excellent in vitro activity against a genotypic cluster of Mup-R isolates from pediatric patients presenting to our institution with MRSA infection. These data suggest that retapamulin may be a promising alternative decolonization therapy for MRSA and a viable option to prevent the spread of mupirocin-resistant MRSA clones. Further research includes an ongoing randomized, placebo-controlled trial testing the in vivo efficacy of retapamulin as a nasal and perirectal decolonizing agent in children. Disclosures: A. Patel, Aqua Pharmaceuticals: Investigator inititiated grant, Research grant. J. Lighter-Fisher, Aqua Pharmaceuticals: Investigator Initiated Grant, Research grant.